Markers of pregnancy: How early can we detect pregnancies in cattle using pregnancy-associated glycoproteins (PAGs) and microRNAs? - Reese, S. T.; Pereira, M. C. [UNESP]; Vasconcelos, J. L.M. [UNESP]; Smith, M. F.; Green, J. A.; Geary, T. W.; Peres, R. F.G. [UNESP]; Perry, G. A.; Pohler, K. G. (Colegio Brasileiro de Reproducao Animal - CBRA, 2016)
Pregnancy detection has evolved over the last few decades and the importance of early pregnancy detection is critical to minimize the amount of time a cow spends not pregnant. Embryonic mortality (EM) is generally considered to be the primary factor limiting pregnancy rates in cattle and occurs early ( < day 28) or late (≥day 28) during gestation (day 0 = estrus). In cattle, the incidence of early EM is approximately 20 to 40% and the incidence of late EM is approximately 3.2 to 42.7%. Significant effort has been directed toward understanding the mechanisms resulting in early EM up to day 17; however, relatively little is known about the causes or mechanisms associated with EM after day 17. Based on work in these areas, numerous investigators are pursuing methods of early pregnancy or EM detection after day 17 of gestation. This review will highlight some of the technology and markers being used for early pregnancy detection and provide evidence for just how early pregnancy can be detected in the bovine. Advancements in early embryonic or pregnancy detection may lead to development of strategies to overcome early gestation losses.
Keywords: Cattle; Embryonic mortality; Placenta; Pregnancy